Integrating phylogenetics, morphology, and osteology to delimit a new species of endemic montane sheep frog (Microhylidae: Hypopachus) from the Lenca Highlands of Honduras. Issue 2 (5th December 2020) - Firneno, Thomas J.; Itgen, Michael W.; Jacobs, Justin L.; Mcdaniels, Chris X.; Luque-Montes, Ileana R.; Wilson, Larry David; Townsend, Josiah H.
Abstract : Due to their conserved morphology, cryptic species have long been problematic for taxonomists. When attempting to assess diversity and delimit species within these taxa, it has been recognized that an integrative approach can be very useful, whereby independent, yet complementary lines of evidence are utilized. New World microhylids (Anura: Microhylidae: Gastrophryninae) of the genera Gastrophryne and Hypopachus have been highly confounding to taxonomists, due to their extreme morphological conservatism, as well as their fossorial nature resulting in a lack of specimens and public genetic information. Currently, two microhylid species are recognized in Honduras: H. barberi and H. variolosus . Here, we integrate three independent lines of evidence (morphology, osteology, and genetics) to examine previously undescribed diversity among populations of H. barberi in the Lenca Highlands of south-western Honduras. Mitochondrial and nuclear DNA identify populations from the Lenca Highlands as being distinct from other populations previously allocated to H. barberi . This distinction is further supported by divergence dating estimates that place the split between these populations and others of H. barberi in the late-Miocene. We also find several significant morphological and osteological differences between H. barberi and Lenca Highlands populations, including extensively reduced ossification in the (especially cranial) skeleton of the Lenca Highland populations. As a result of these distinctions, we formally describe the Lenca sheep frog as a new species, Hypopachus guancasco sp. nov. http://zoobank.org/urn:lsid:zoobank.org:pub:2B2B4942-2925-42C8-8329-431F55B41AA3